Health Behaviors, Knowledge, Life Satisfaction, and Wellbeing in People with Mental Illness across Four Countries and Comparisons with Normative Sample - Parletta, Natalie; Aljeesh, Yousef; Baune, Bernhard T. (Frontiers in Psychiatry, 2016)
Background: People with chronic mental illness have poorer physical health and higher mortality than the general population. We investigated lifestyle factors in people with mental illness across four countries and compared with a normative sample. Design and methods: Data were collected from N=672 people (Germany, n=375; Palestine, n=192; London, n=63; Australia, n=42) with substance abuse disorder (n=224), schizophrenia (n=158), mood disorders (n=227) and somatoform disorders (n=63). The General Health Behaviour Questionnaire measured behaviours and knowledge related to nutrition, physical activity, alcohol, smoking, sleep, life satisfaction and wellbeing. The normative sample were derived from a German population (N=1,019). Data were analysed using ANOVAs and t-tests. Results: The Palestine sample did not differ from the Western samples on reported life satisfaction and wellbeing. However they reported unhealthier diets, less physical activity, and lower knowledge about the impact of diet, physical activity, smoking and sleep on health than the Western samples. Comparing the Western and normative samples, people with mental illness reported lower intake of healthy foods/drinks, higher intake of unhealthy foods, higher exercise, higher alcohol consumption, smoked less cigarettes, had less sleep and reported more sleep problems. Their knowledge was lower for nutrition, physical activity, and smoking. All participants reported lower life satisfaction and wellbeing than the normative sample (P values <0.001). Conclusions: Education on health-related lifestyle factors present important targets for primary care, quality of life and prevention of illness in people with mental illness. Further research will clarify specific predictors of health behaviours in each country.